Multilevel Data Encryption Using Thermal‐Treatment Controlled Room Temperature Phosphorescence of Carbon Dot/Polyvinylalcohol Composites. Issue 9 (31st July 2018) - Tian, Zhen; Li, Di; Ushakova, Elena V.; Maslov, Vladimir G.; Zhou, Ding; Jing, Pengtao; Shen, Dezhen; Qu, Songnan; Rogach, Andrey L.
Abstract: Thermal‐treatment controlled room temperature phosphorescence is realized by embedding either originally synthesized carbon dots (CDs) or 200 °C thermal‐treated CDs into a polyvinylalcohol (PVA) matrix through post‐synthetic thermal annealing at 200 or 150 °C. The thermal‐treatment controlled phosphorescence is attributed to the transfer of photoexcitation from the excited singlet state to the triplet state through intersystem crossing, followed by radiative transition to the ground state, which is due to decrease of quenchers (oxygen) in the CDs and suppression of the vibrational dissipations through the chemical bonding of CDs in the PVA matrix. Multilevel fluorescence/phosphorescence data encryption is demonstrated based on the thermal‐treatment controlled phosphorescence from CD@PVA composites. Abstract : Multilevel data encryption by thermal‐treatment controlled phosphorescence is realized by chemical bonding of carbon dots (CDs) in a polyvinylalcohol (PVA) matrix, which suppresses the vibrational dissipation of the triplet state. The occurrence of the phosphorescence is attributed to the intersystem crossing of excitation transportation from the singlet state in the core of the CDs to the triplet state in emitting centers on the surface.